Safety and efficacy of a feed additive consisting of l‐valine produced with Corynebacterium glutamicum KCCM 80365 for all animal species (CJ Europe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, the European Food Safety Authority (EFSA) was asked to deliver a scientific opinion on the safety and efficacy of l‐valine produced with a genetically modified strain of Corynebacterium glutamicum (KCCM 80365) when used as a nutritional additive in feed and water for drinking for all animal species and categories. l‐Valine manufactured by fermentation using C. glutamicum KCCM 80365 does not give rise to any safety concern regarding the genetic modifications of the production strain. No viable cells or DNA of the production strain were detected in the final product. The use of l‐valine produced with C. glutamicum KCCM 80365 in feed is safe for the target species when supplemented in appropriate amounts to the diet according to the nutritional needs of the species. The FEEDAP Panel has concerns on the use of l‐valine in water for drinking. The use of l‐valine produced by fermentation with C. glutamicum KCCM 80365 in animal nutrition is considered safe for the consumers and for the environment. l‐Valine produced with C. glutamicum KCCM 80365 is not irritant to skin and eyes, nor considered a skin sensitiser. The additive l‐valine is regarded as an effective source of the amino acid l‐valine for all non‐ruminant species. To be as efficacious in ruminants as in non‐ruminants, it should be protected from ruminal degradation.